THE IMPLEMENTATION OF COOPERATIVE PRINCIPLE IN CLASS GROUP DISCUSSION - Juansah, Dase Erwin; Emzir, E (PPs UNJ, 2016)
This study is aimed to understand the implementation of Griceâs cooperative principle in class group discussion at Indonesian Language and Literature Study Program of Faculty of Teachers Training and Education of UNTIRTA Serang. The research was conducted through ethnographic study. Data of the research were collected through observation and transcription of documentation which investigated into the analysis of domain, taxonomy, componential, and cultural themes. The result of study showed that the implementation of Griceâs cooperative principles was found in class group discussion at Indonesian Language and Literature Study Program of Faculty of Teachers Training and Education of UNTIRTA Serang. The maxim that mostly occurred was maxim of quantity, continued by maxim of relevance, maxim of quality, and maxim of manner. The result also showed that the use of cooperative principles in class group discussion could not be separated from the influence of studentsâ origin culture and mother tongue which reflected into the use of formal language, politeness, tone, sense of respect and focus on the discussion, and the use direct speech.